Avaliação epidemiológica molecular de cepas do Mycobacterium tuberculosis provenientes de Minas Gerais - Claudio Jose Augusto (2014)
In Brazil, are registered for year about 71.000 new tuberculosis cases, with incidence coefficient of 36.7 cases/100mil inhabitants and 4.600 deaths, being the country in 16º place between 22 countries with 80% of load of the disease in the world. In Minas Gerais in 2007 year were identified 4.810 new tuberculosis cases with an incidence coefficient of 25 cases/100mil inhabitants and 276 deaths. At this scene, know about disease epidemiological characteristics and the genetic diversity of Mycobacterium tuberculosis clinical isolates can be useful for information about circulating strains origin and transmission. Molecular techniques of DNA M. tuberculosis genotyping has been very used for epidemiologic relations investigation between tuberculosis cases since 1990 decade, as Restriction Fragment Length Polymorfism - RFLP-IS6110, that revolutionized the studies about M. tuberculosis transmission and the Variable Number Tandem Repeat Mycobaterial Interspersed Repetitive Units MIRU-VNTR. The main objectives of this study were: Genotype Mycobacterium tuberculosis strains isolated of patients diagnosed as new TB cases and evaluate the genetic variability of these strains. Analyze the profile of TB cases in Minas Gerais according with sociodemographic, clinical and laboratorial characteristics. Compare the similarity degree between M. tuberculosis strains using RFLPIS6110 and MIRU-VNTR techniques. Evaluate clinical-demographics data between patients with M. tuberculosis strains resistant or sensitive in relation at drugs considered as new cases and the bacillus molecular profile. Evaluate presence of epidemiological bond in cases of M. tuberculosis strains characterized as cluster. The methods for have these objectives and the results were submitted in two original articles resumed as follow. Original Article 1: Analyze the tuberculosis (TB) profile in Minas Gerais/Brazil, according sociodemographic, clinical, laboratorial, comorbidities and mortality characteristics during the 2002 to 2009 period. Epidemiological, descriptive study, with lifting of data of notified cases in Information System of Notifiable Diseases (SINAN) and System of Mortality Information (SIM), in 2000 to 2009 period. It was notified 47.285 TB cases in the years studied, with an average of incidence 22,3 /100 mil inhabitants. The biggest frequency was from age of 20 to 49 years (62,4%), male (67,0%) and low schooling (18,5%). The new cases represented (84,3%), the relapse (5,7%), reentry after abandonment (5,7%) e DOTS (21,8%). The cure was (66,2%), treatment abandon (11,2%), TB multirresistance (0,2%) and mortality of (12,9%). The baciloscopy exams and culture were requested in 26,1% and 87,1% of the cases, respectively. The chest radiogram was performed in 90,5%. The pulmonary form had higher incidence (83,9%). In relation of comorbidities were observed the alcoholism in (15,0%) of notified cases, the Human Immunodeficiency Virus in (8,4%) and Diabetes mellitus in (3,7%). The new cases incidence, the abandonment, the TB mortality are high, the comorbidities are relevant and the bacteriological exams are not accordingly performed for TB diagnostic. It is necessary a multiprofessional study, treatment magnification directly observed (DOTS) and knowledge of the disease distribution in state with improvement and association with data bank SIM e SINAN, to have better TB control in Minas Gerais. Original Article 2: The genotyping of M. tuberculosis has being broadly applied for epidemiological relations investigation between tuberculosis cases, in many countries since that DNA typing techniques were developed in 1990 decade as the Restriction Fragment Length Polymorfism - RFLP-IS6110 and the Variable Number Tandem Repeat Mycobacterial Interspersed Repetitive Units - MIRUVNTR with12 and 24 locus. The application of these methods has highly advanced the knowledge about the transmission and/or important pathogenic properties of mycobacterial and provides new and powerful tools to combat and protect against diseases caused for this pathogens. This study has as objective genotype M. tuberculosis strains isolated of patients diagnosed as new TB cases in Minas Gerais and compare the RFLP-IS6110 e MIRU-VNTR 12 loci techniques results. It is a retrospective transversal study with analyses of M. tuberculosis strains isolated from new TB cases in 2007 in Minas Gerais, using molecular techniques RFLP-IS6110 e MIRU-VNTR to analyze the similarity, the discriminatory power, concordances and cluster formation between these techniques. Strains with RFLP-IS6110 e MIRU-VNTR profile with similarity superior to 85% were considered of the same family. From samples, 32,3% were similar by RFLP-IS6110 and 50,9% by MIRU-VNTR. The discriminatory levels of the two methods dont differ substantially: RFLP-IS6110 resulted in 191 distinct profiles in comparison with 176 by MIRU-VNTR. The global concordance, defined as isolates of unique profiles or identically distributed in groups for both methods, was 87,7% (179/204), being considered 171 as unique profiles and 8 isolates in cluster. From remaining 25 cases, 2,5%(5/204) cases were grouped only by RFLP-IS6110 and 9,8% (20/204) only by MIRU-VNTR The RFLP-IS6110 cluster tax was also smaller than the MIRU-VNTR, being 3,2% and 4,3% respectively. The epidemiological relation between the grouped strains were confirmed in 4 patients (31%) in RFLP-IS6110 in comparison with 14% in MIRU-VNTR We concluded that few isolates were similar. The RFLP-IS6110 showed highly discriminatory being to be used in Minas Gerais. The comparisons between the two techniques showed the RFLP-IS6110 discriminatory power lightly superior to MIRU-VNTR and have higher epidemiological relation when the clusters were analyzed.